Caffeine consumption and the effects on university students’ performances in Petaling, Selangor - Abdul Aziz, Ainul Hayati; Zaidan, Amelia; Abdul Latib, Nur Farrah Yasmin; Md Rus, Mohammad Hafizi (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
This study examines caffeine consumption and its effects on university students’ performance in Petaling, Selangor. Caffeine has long been associated with enhancing cognitive functions and improving task performance. Many students rely on caffeinated beverages to cope with academic pressure and maintain productivity, yet their overall impact remains debated. To explore this issue, 400 survey responses were collected through a self-administered questionnaire from students attending public and private universities in Petaling, Selangor. Findings indicate that caffeine consumption positively influences academic performance by extending study time, assisting in task completion, and enhancing attentiveness in class. Coffee emerged as the most common source of caffeine among students. This study highlights the role of caffeine in supporting student performance and offers a basis for future research to explore caffeine consumption among students across different regions of Malaysia, where the topic remains underexplored.